Williams, Florence (2017). The nature fix: Why nature makes us happier, healthier, and more creative - Vich, Guillem (Documents d’Anàlisi Geogràfica, 2019)
Williams, Florence (2017) The nature fix: Why nature makes us happier, healthier, and more creative Nova York: W. W. Norton Company, 304 p. ISBN 978-0-393-24271-3